(untitled) (Indo-MathEdu Intellectuals Journal, 2024)
This research is based on the low learning outcomes of science science in grade IV students of SDN 07 Sigiran, Malalak District, Agam Regency. This study aims to describe the Improvement of Science and Technology Learning Outcomes in Grade IV Students with a Guided Inquiry Model at SDN 07 Sigiran, Malalak District, Agam Regency. This research is classroom action research carried out in four stages, namely planning, implementation, observation, and reflection. The data collection techniques are test and non-test. The subjects of the study were teachers and students of grade IV of SDN 07 Sigiran, Malalak District, Agam Regency. The results of the study show that the assessment of the teaching module in the first cycle, which is 83.32% (B), increased in the second cycle to 94.44% (SB). The assessment of teacher activity in the first cycle was 83.32% (B), increasing in the second cycle to 97.22% (SB). The assessment of student activity in the first cycle was 80.55% (B), increasing in the second cycle to 94.44% (SB). The learning outcomes of students in the attitude aspect in the first cycle were obtained on average, which was 82.99 (B), increasing in the second cycle to 84 (B). The learning outcomes of students in the knowledge aspect in the first cycle were obtained on average, namely 73.52 (C), increasing in the second cycle to 81.17 (B). The learning outcomes of students in the skill aspect were obtained on average, which was 74.52 (C) increasing in the second cycle to 82.76 (B), so it can be concluded that the guided inquiry model can improve the learning outcomes of social studies in Grade IV students at SDN 07 Sigiran